2015
DOI: 10.4137/bcbcr.s23794
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Survival Benchmark for Breast Cancer Patients with Systemic Relapse

Abstract: BACKGROUNDOur original paper, published in 1992, reported a median overall survival after first relapse in breast cancer of 26 months. The current retrospective review concentrates more specifically on patients with first systemic relapse, recognizing that subsets of patients with local recurrence are potentially curable.METHODSRecords of 5,168 patients from a largely breast-cancer-specific oncology practice were reviewed to identify breast cancer patients with their first relapse between 1996 and 2006 after p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 29 publications
0
17
0
1
Order By: Relevance
“…We repeated this analysis for the eight studies (28–32,35,37,49,50) that collected data on unadjusted survival after recurrence separately for ER-positive (3073 patients) and ER-negative disease (1239 patients) (Table 2, Figure 3, B and C). Although numbers were smaller than for recurrent disease as a whole, we observed similar trends in survival improvement over time in ER-positive and ER-negative recurrent disease: from 1980 to 1990, the median survival ratio was 1.08 (95% CI = 0.66 to 1.79; P = 0.75) for ER-positive disease and 0.95 (95% CI = 0.55 to 1.66; P = 0.87) for ER-negative disease; from 1990 to 2000, the median survival ratio was 1.25 (95% CI = 1.05 to 1.49; P = .014) for ER-positive disease and 1.30 (95% CI = 1.08 to 1.57; P = .007) for ER-negative disease; and from 2000 to 2010, the median survival ratio was 1.44 (95% CI = 0.93 to 2.21; P = .10) for ER-positive disease and 1.77 (95% CI = 1.13 to 2.79; P = .01) for ER-negative disease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We repeated this analysis for the eight studies (28–32,35,37,49,50) that collected data on unadjusted survival after recurrence separately for ER-positive (3073 patients) and ER-negative disease (1239 patients) (Table 2, Figure 3, B and C). Although numbers were smaller than for recurrent disease as a whole, we observed similar trends in survival improvement over time in ER-positive and ER-negative recurrent disease: from 1980 to 1990, the median survival ratio was 1.08 (95% CI = 0.66 to 1.79; P = 0.75) for ER-positive disease and 0.95 (95% CI = 0.55 to 1.66; P = 0.87) for ER-negative disease; from 1990 to 2000, the median survival ratio was 1.25 (95% CI = 1.05 to 1.49; P = .014) for ER-positive disease and 1.30 (95% CI = 1.08 to 1.57; P = .007) for ER-negative disease; and from 2000 to 2010, the median survival ratio was 1.44 (95% CI = 0.93 to 2.21; P = .10) for ER-positive disease and 1.77 (95% CI = 1.13 to 2.79; P = .01) for ER-negative disease.…”
Section: Resultsmentioning
confidence: 99%
“…First, only three of the studies we analyzed reported data on HER2 status, so we cannot determine how much the success of HER2-targeted therapies may have contributed to our findings for ER-positive and ER-negative breast cancer. However, because HER2-positive cancers were the minority in studies that reported HER2 (<30%) (28,50,61), they are unlikely to account for all of the observed survival improvement, suggesting that improvement has been made in triple-negative disease as well. Similarly, only one-quarter of the patients analyzed for recurrent disease had ER status available, decreasing the precision of estimates by ER status.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the tumour mass and tumour biology, breast cancer patients have highly varied prognoses 1 , 2 . In about 15% of breast cancers, there is neither expression of the estrogen (ER) and progesterone receptor (PgR) (≤ 1%) nor an overexpression or amplification of the human epidermal growth factor receptor (HER) 2 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Brustkrebspatientinnen haben in Abhängigkeit von Tumormasse und Tumorbiologie eine sehr unterschiedliche Prognose 1 , 2 . Bei etwa 15% der Mammakarzinome liegen weder eine Expression des Östrogen-(ER-) und Progesteronrezeptors (PgR) (≤ 1%) noch eine Überexpression bzw.…”
Section: Introductionunclassified
“…The 5-year overall survival rates among patients with axillary, supraclavicular, and internal mammary lymph node (IMN) recurrences are limited to 24% to 35% 1, 2. IMN involvement has been reported to comprise only 1% of patients with locoregional failures 4, 5. Advances in radiographic imaging, however, suggest that IMN failures may have been underdetected because FDG (fludeoxyglucose)–positron emission tomography and magnetic resonance imaging improve the detection of IMN metastases not identified on conventional chest imaging 6, 7…”
Section: Introductionmentioning
confidence: 99%